Identifying social indicators for the BRICS using public data: an investigation of the school dropout phenomenon in Brazil, India and South Africa - Chetty, Krish (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPhil)--Stellenbosch University, 2017.